Apple : skin to the core : a memoir in words and pictures - Gansworth, Eric., 1965- (Levine Querido, 2020)
"The term "Apple" is a slur in Native communities across the country. It's for someone supposedly "red on the outside, white on the inside." Eric Gansworth is telling his story in Apple (Skin to the Core). The story of his family, of Onondaga among Tuscaroras, of Native folks everywhere. From the horrible legacy of the government boarding schools, to a boy watching his siblings leave and return and leave again, to a young man fighting to be an artist who balances multiple worlds. Eric shatters that slur and reclaims it in verse and prose and imagery that truly lives up to the word heartbreaking." -- Inside front jacket flap.